Mixing the Code in the Speech of the Community of Ulunambo Village, Menui Islands District - Putri Nurul Fadilah; Syamsuddin Syamsuddin; Arum Pujining Tyas; Mohammad Tahir; Idris Patekkai (Civiliza Publishing, Indonesia., 2026)
In the development of contemporary linguistics, the study of syntax focuses not only on the relationships between words in sentences, but also on how the syntactic structure represents the thinking patterns and characteristics of a language community. This study aims to describe the form and causes of code mixing in the speech of the people of Ulunambo Village, Menui Islands District. This research uses a qualitative method. This study uses primary data as the main type and source of data. The primary data was obtained directly from the people of Ulunambo Village through the process of collecting data in the field. The data in question is in the form of natural speech that appears in daily interactions. The research data was obtained through observation, listening, recording, and recording techniques with the research subjects of the community of Ulunambo Village, Menui Islands District. Data analysis is carried out through three stages, namely data condensation, data presentation, and conclusion drawn. The results of the study showed that the form of code mixing found included a mix of word, phrase, and clause level codes. The mixing of the code occurs due to speaker factors and linguistic factors. Speaker factors include language habits and social closeness in daily interactions, while linguistic factors include the need for accuracy and efficiency of meaning in speech delivery.